2016
DOI: 10.2217/bmm-2016-0130
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_Circrna_103636: Potential Novel Diagnostic and Therapeutic Biomarker in Major Depressive Disorder

Abstract: These results suggest that altered expression of hsa_circRNA_103636 in PBMCs is a potential novel biomarker for the diagnosis and treatment of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 45 publications
0
78
0
1
Order By: Relevance
“…Serum/plasma is the most commonly used biological specimen for in-vitro diagnosis because of its nature of easy to obtain. However, because the abundance of circRNAs is significant higher in PBMCs than in serum/plasma and it’s relatively easy to obtain, PBMCs are the most commonly used sample for circRNAs detection [13, 17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum/plasma is the most commonly used biological specimen for in-vitro diagnosis because of its nature of easy to obtain. However, because the abundance of circRNAs is significant higher in PBMCs than in serum/plasma and it’s relatively easy to obtain, PBMCs are the most commonly used sample for circRNAs detection [13, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent researches showed that circRNAs can function as potential molecular markers for disease diagnosis. For example, Cui et al showed that hsa_circRNA_103636 in peripheral blood mononuclear cells (PBMCs) can be used as a novel biomarker for the diagnosis and treatment of major depressive disorder [13], Chen et al found that hsa_circ_0000190 could be used as a new biomarker for gastric cancer [14], and Zhao et al discovered that hsa_circ_0124644 in peripheral blood can be used as a diagnostic biomarker for coronary artery disease [15]. However, there is no report regarding the use of circRNAs as biomarkers for TB.…”
Section: Introductionmentioning
confidence: 99%
“…This confers resistance to RNase R treatment, allowing circRNAs to be selectively enriched during sample processing and making them more suitable biomarkers than other types of RNA [7-9]. Studies demonstrated that circRNAs are involved in the development of several diseases, such as cancer [10-12], Alzheimer’s disease [13], major depressive disorder [14], atherosclerotic vascular disease [15], and pre-eclampsia [16]. Recent studies have found that circRNAs can bind to microRNAs (miRNAs) and act as “miRNA sponges” by sequestering target miRNAs and preventing them from regulating other endogenous target genes.…”
Section: Introductionmentioning
confidence: 99%
“…10 Research have shown that lncRNAs play a significant role in many life activities, such as dose-compensating effects, 11 epigenetic regulation, 12 regulation of cell cycle, 13 and regulation of cell differentiation 14 and has become a focus of genetic research. 16,17 Some studies have shown that X-inactive specific transcript (XIST) can be involved in the occurrence of gastric cancer, bladder cancer, 18,19 but the specific mechanism of XIST in bladder cancer is still not clear. 16,17 Some studies have shown that X-inactive specific transcript (XIST) can be involved in the occurrence of gastric cancer, bladder cancer, 18,19 but the specific mechanism of XIST in bladder cancer is still not clear.…”
Section: Introductionmentioning
confidence: 99%